Genomic Analysis of Phylotype I Strain EP1 Reveals Substantial Divergence from Other Strains in the Ralstonia solanacearum Species Complex - Li, Peng; Wang, Dechen; Yan, Jinli; Zhou, Jianuan; Deng, Yinyue; Jiang, Zide; Cao, Bihao; He, Zifu; Zhang, Lianhui (Frontiers in Microbiology, 2016)
Ralstonia solanacearum species complex is a devastating family of phytopathogens with an unusually wide host range and broad geographical distribution. R. solanacearum isolates may differ considerably in various properties including host range and pathogenicity, but the genetic background behind variation remains vague. Here, we conducted the genome sequencing of strain EP1 isolated from Guangdong Province of China, which belongs to phylotype I and is highly virulent to a range of solanaceous crops. Its complete genome contains a 3.95-Mb chromosome and a 2.05-Mb mega-plasmid, which is considerably bigger than other reported genomes of R. solanacearum strains, both chromosome and mega-plasmid have essential house-keeping genes and many virulence genes. Comparative analysis of strain EP1 with other 3 phylotype I and 3 phylotype II, III, VI strains unveiled substantial sequence rearrangement, insertions and deletions among them. Genome sequences are relatively conserved among the 4 phylotype I strains, but less conserved in the different phylotype strains. Moreover, distinct variance and diversities were found among different strains in the key virulence genes, including those encoding secretion systems and type III effectors. Our results would be useful in further analysis of genetic basis of variation in virulence and host range of the R. solanacearum species.